DNA methylation profiling across brain regions in Huntington's disease. (20th December 2022) - Wheildon, Greg; Weymouth, Luke Stephen; Smith, Adam R.; Smith, Rebecca G.; Troakes, Claire; Al‐Sarraj, Safa; Lunnon, Katie
Abstract: Background: Huntington's disease (HD) is an autosomal dominant condition that occurs due to the expansion of a CAG trinucleotide repeat in the Huntingtin (HTT) gene. The translated HTT protein has an expanded polyglutamine sequence thought to cause deleterious effects. These effects cause severe neurodegeneration in the striatum. In HD there is also clear atrophy in the cerebellum and a reduction in cortical thickness, including in the entorhinal cortex (EC). Epigenome wide association studies (EWAS) of DNA methylation differences in HD have thus far been limited to the cerebral cortex and use older technologies such as the Illumina 450K array. In this study, we performed an EWAS of HD in the striatum, EC and cerebellum, using the Illumina EPIC methylation array to profile 850, 000 sites across the genome. Method: 120 striatum, EC and cerebellum DNA samples from 22 control and 20 HD subjects were selected and matched for sex, age and post‐mortem interval. The samples were chosen to be as free from co‐existing pathologies as possible. The majority of subjects were represented in each brain region. The DNA was bisulfite converted, randomized and profiled using the EPIC array. The methylation intensities for each sample were subjected to quality control (QC). Following QC, the samples were analyzed in R for differences in methylation between HD and control samples within each brain region, before being subjected to cross‐regional analysis. Result: We have used linear regression models to identify differentially methylated positions (DMPs) in specific brain regions in HD. We have used regional analyses to identify differentially methylated regions (DMRs) consisting of multiple adjacent DMPs. Finally, downstream analyses have highlighted epigenetically altered pathways in disease. Conclusion: This study builds a clearer picture of DNA methylation profiles in HD in disease relevant brain regions. Future studies should integrate this with other levels of genomic regulation.